The Impact of Appealing Dish Names on Plant-Based Food Choices in Corporate Cafes: A Field Study. (29th May 2020) - Gavrieli, Anna; Attwood, Sophie; Stillman, Paul; Putnam-Farr, Eleanor; Wise, Jonathan; Upritchard, Jane; Hanson, Chavanne; Bakker, Michiel
Abstract: Objectives: Companies are looking to support their employees with healthier and more sustainable food options. Here, we test if appealing dish names could influence food choices at corporate cafes. We hypothesized that menu items accompanied by appealing food names would be selected more compared to when accompanied by basic names. Methods: The study had a quasi experimental design and was conducted in buffetera-style cafes in four corporate offices across the world (Sydney, Chicago, Singapore & Sao Paulo) where food is complementary. The seated head count at these offices is ∼850–2500 employees. Three plant-based menu items including entrees, side dishes, composed salads and/or soups were tested at each site. Appealing names were generated through a creative workshop and emphasized the dish ingredients, origin, flavor and/or the eating experience. Each menu item appeared 4 to 6 times across repeated menu cycles, 4 weeks apart one from another, with the dish name alternating between basic and appealing across dish repetitions. For each dish, we weighed the overall food take and divided it by the plate count to estimate food taken per plate in the cafe. Data was analysed using the lme4 package in R and are presented as median (Q1, Q3). Results: Overall, appealing dish names increased the food amount taken per plate by 35% when compared to the basic dish names [23.5 (12.7, 40.7) vs. 17.3 (10.7, 37.6) g/plate, respectively] with the effect being marginally significant [ b = 2.90, SE = 1.6, t (46.25) = 1.80, P = 0.078]. Conclusions: The findings indicate that making dish names more appealing has the potential to cause an uplift in the dishes; making this a promising strategy to shift food choices towards more plant-based options. This relatively easy change could help foodservice providers to support more sustainable and healthier food choices. Funding Sources: The study was funded by Google Inc.